Implementation of Primary Health Care Integration (ILP) to enhance cadre competence and posyandu service standards - Kusuma Estu Werdani; Dwi Linna Suswardany; Dian Hudiyawati; Windi Wulandari; Beti Kristinawati; Yeni Indriyani; Anggi Putri Aria Gita (University of Merdeka Malang, 2026)
The Integration of Primary Health Care (ILP) requires posyandu cadres to be competent in delivering life-course–based health services. In Tawang Village, Weru Subdistrict, Sukoharjo Regency, none of the posyandu cadres had received ILP training, so no posyandu in the village was able to operate ILP-standard services. This community service program aimed to improve the knowledge and basic skills of Tawang Village posyandu cadres so that they are prepared to deliver ILP-standard posyandu services. The program involved 37 cadres from five posyandu and was carried out in three stages: ILP education, mentoring of ILP service practice using the five-table system, and evaluation of cadre knowledge and basic skills. The cadres' knowledge was already good before the activity (median 92) and became higher and more uniform afterwards (median 96), with a statistically significant difference (p = 0.013). Skill mapping showed that 37.9 percent of cadres reached the “utama” (advanced) category, 29.7 percent “madya” (intermediate), and 32.4 percent “purwa” (novice), revealing skill gaps between posyandu. As an impact, the activity produced a cadre competency map that enables the village midwife and Weru Public Health Center to provide targeted mentoring so that all five posyandu in Tawang Village can meet ILP service standards. Tiered mentoring is recommended, prioritising posyandu with a high proportion of basic-level cadres.